The EFFECT OF GIVING MUNG BEAN EXTRACT TO POST-PRACTICE MOTHERS ON BREAST MILK PRODUCTION - Zelharsandy, Vika Tri; Ciselia, Dewi; Fatrin, Tiara (Jurnal Kesehatan Abdurrahman, 2026)
The postpartum period is a 40-day recovery period for the reproductive organs. Breast milk is the best food for babies because it contains so many benefits for babies. Breast milk (Mother's Milk) is the only natural, best food for babies. Breast milk contains various nutrients needed for growth and development. The benefits of breast milk are very large, including increasing the growth of brain nerve cells, reducing the risk of babies suffering from diseases, and providing a loving relationship between mother and baby. One way to increase breast milk production is by consuming mung bean juice. Mung beans contain 20-25% protein. Mothers need a lot of protein during breastfeeding because protein contains amino acids that can stimulate breast milk secretion. The purpose of this study was to determine the effect of giving mung bean juice to postpartum mothers on breast milk production. This study used a quasi-experimental design with a one-group pre-post design and a sampling technique using total sampling. In this study, there were 15 respondents. This study was conducted from December 2024 to January 2025. The results showed that the average breast milk production in postpartum mothers before being given mung bean juice was 1.47, and after being given mung bean juice, it increased by 2.47. Based on the results of the Wilcoxon rank test, the Asymp. Sign (2-tailed) value was 0.005 <α (0.05). Therefore, Ha was accepted, thus concluding that there was a significant difference between postpartum mothers' breast milk production before and after being given mung bean juice to postpartum mothers. Keywords: postpartum mothers, breast milk production, green bean extract